The Fixpoint Bounded-Variable Queries are PSPACE-Complete - Dziembowski, Stefan (BRICS Report Series, 1996)
We study complexity of the evaluation of fixpoint bounded-variable queries in relational databases. We exhibit a finite database such that the problem whether a closed fixpoint formula using only 2 individual variables is satisfied in this database is PSPACE-complete. This clarifies the issues raised by Moshe Vardi in [Var95]. We study also the complexity of query evaluation for a number of restrictions of fixpoint logic. In particular we exhibit a sublogic for which the upper bound postulated by Vardi holds.